The Role of Programmed Cell Death Regulator LSD1 in Nematode-Induced Syncytium Formation - Matuszkiewicz, Mateusz; Sobczak, Miroslaw; Cabrera, Javier; Escobar, Carolina; Karpiński, Stanislaw; Filipecki, Marcin (Frontiers in Plant Science, 2018)
Cyst-forming plant-parasitic nematodes are common pests of many crops. They inject secretions into host cells to induce the developmental and metabolic reprogramming that leads to the formation of a syncytium, which is the sole food source for growing nematodes. As in other host-parasite models, avirulence leads to rapid and local programmed cell death (PCD) known as the hypersensitive response (HR), whereas in the case of virulence, PCD is still observed but is limited to only some cells. Several regulators of PCD were analyzed to understand the role of PCD in compatible plant-nematode interactions. Thus, Arabidopsis plants carrying recessive mutations in LESION SIMULATING DISEASE1 (LSD1) family genes were subjected to nematode infection assays with juveniles of Heterodera schachtii. LSD1 is a negative and conditional regulator of PCD, and fewer and smaller syncytia were induced in the roots of lsd1 mutants than in wild-type Col-0 plants. Mutation in LSD ONE LIKE2 (LOL2) revealed a pattern of susceptibility to Heterodera schachtii antagonistic to lsd1. Syncytia induced on lsd1 roots compared to Col0 showed significantly retarded growth, modified cell wall structure, increased vesiculation, and some myelin-like bodies present at 7 and 12 days post-infection. To place these data in a wider context, RNA-sequencing analysis of infected and uninfected roots was conducted. During nematode infection, the number of transcripts with changed expression in lsd1 was approximately three times smaller than in wild-type plants (1440 versus 4206 differentially expressed genes, respectively). LSD1-dependent PCD in roots is thus a highly regulated process in compatible plant-nematode interactions. Two genes identified in this analysis, coding for AUTOPHAGY-RELATED PROTEIN 8F and 8H were down-regulated in syncytia in the presence of LSD1 and showed an increased susceptibility to nematode infection contrasting with lsd1 phenotype. Our data indicate that molecular regulators belonging to the LSD1 family play an important role in precise balancing of diverse PCD players during syncytium development required for successful nematode parasitism.